2020
DOI: 10.20944/preprints202004.0299.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remdesivir: A Review of Its Discovery and Development Leading to Human Clinical Trials for Treatment of COVID-19

Abstract: The global pandemic of SARS-CoV-2, the causative viral pathogen of COVID-19, has driven the biomedical community to action – to uncover and develop anti-viral interventions. One potential therapeutic approach currently being evaluated in numerous clinical trials is the agent remdesivir, which has endured a long and winding developmental path. Remdesivir is a nucleotide analog prodrug that perturbs viral replication, originally evaluated in clinical trials to thwart the Ebola outbreak in 2014. Subsequ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…Remdesivir suppresses viral replication and it was initially tested in clinical trials to prevent the 2014 Ebola outbreak. Later investigations indicated Remdesivir's ability to inhibit replication of coronavirus, including SARS-CoV-2 as well [32]. In another cohort study, medical progress was observed in 68% of patients taken to the hospital with severe COVID-19 treated with Remdesivir [33].…”
Section: Rna-dependent Rna Polymerase Inhibitorsmentioning
confidence: 99%
“…Remdesivir suppresses viral replication and it was initially tested in clinical trials to prevent the 2014 Ebola outbreak. Later investigations indicated Remdesivir's ability to inhibit replication of coronavirus, including SARS-CoV-2 as well [32]. In another cohort study, medical progress was observed in 68% of patients taken to the hospital with severe COVID-19 treated with Remdesivir [33].…”
Section: Rna-dependent Rna Polymerase Inhibitorsmentioning
confidence: 99%
“…Currently, there are several clinically approved antiviral drugs under consideration to find effective treatments targeting viral entry and replications. These include an oral drug called EIDD-2801, anti-malarial drug hydroxychloroquine, remdesivir -a failed Ebola drug, and kaletra which is a combination of HIV drug lopinavir and ritonavir [22][23][24][25]. Not just anti-viral drugs, but immunosuppressants like sarilumab and tocilizumab are also being tested for the patients, where not only the virus but the patient's immune overreaction worsens the situation ultimately killing them [26].…”
Section: Potential Treatmentmentioning
confidence: 99%
“…Potential drug candidates for COVID-19 therapy are continuously substituted and changed, similar to basketball players in the last minutes of the final game to save the championship. Remdesivir, the most awaited and most promising candidate, has been fervently supported by doctors and politicians as a potential cure for COVID-19 [129] but appears to be inefficient according to the first randomized trial (158 patients) in China on patients with severe COVID-19 symptoms [130]. In addition, it was found that a high dosage of remdesivir may induce testicular toxicity and result in deterioration of sperm parameters in mice [131].…”
Section: Post Datummentioning
confidence: 99%